Feeling coerced during voluntary and involuntary psychiatric hospitalisation: A review and meta-aggregation of qualitative studies. Issue 2 (February 2023) - Silva, Benedetta; Bachelard, Mizue; Amoussou, Joëlle Rosselet; Martinez, Debora; Bonalumi, Charlotte; Bonsack, Charles; Golay, Philippe; Morandi, Stéphane
Abstract: Objective: This review aimed to provide an aggregative synthesis of the qualitative evidence on patients' experienced coercion during voluntary and involuntary psychiatric hospitalisation. Design: A qualitative review. Data sources: The search was conducted, in five bibliographic databases: Embase.com, Ovid MEDLINE(R) ALL, APA PsycINFO Ovid, Web of Science Core Collection and the Cochrane Database of Systematic Reviews. Review methods: Following the Joanna Briggs Institute approach, a systematized procedure was applied throughout the review process, from data search to synthesis of results. The reporting of this review was guided by the standards of the PRISMA 2020 statement. The quality of the included studies was critically appraised by two independent reviewers using the JBI Critical Appraisal Checklist. Included findings were synthesized using meta-aggregation. Confidence in the review findings was assessed following the Confidence in the Output of Qualitative research synthesis (ConQual) approach. Results: A total of 423 studies were identified through the literature search and 26 were included in the meta-aggregation. Totally, 151 findings were extracted and aggregated into 27 categories and 7 synthesized findings. The synthesized findings focused on: the patients' experience of the hospitalisation and the associated feeling of coercion; the factors affecting this feeling, such as the involvement in the decision-making process, the relationships with the staff and the perception of the hospital treatment as effective and safe; the coping strategies adopted to deal with it and the patients' suggestions for alternatives. All synthesized findings reached an overall confidence score of "moderate". The seven findings were downgraded one level due to dependability limitations of the included studies. Conclusion: Based on these findings, seven recommendations for clinical practice where developed, such as fostering care ethics, promoting patients' voice and shared decision-making, and enhancing patients' perceived closeness, respect and fairness. Five recommendations for future research were also prompted, for instance improving the methodological quality and cultural variation of future qualitative studies, and exploring the psychosocial impact of experienced coercion on patients. For these recommendations to be effectively implemented, a profound change in the structure and culture of the mental health system should be promoted. The involvement of patients in the design, development and scientific evaluation of this change is strongly recommended.